Porous space — biomimetic of tafoni in computational design - Ye, Wei; Chen, Shuhua; Zhao, Xiayu; Xu, Weiguo (Architectural intelligence, 2022)
Porous urban spaces not only improve interactions, but also increase natural ventilation. Weathered rocks are where porous spaces exist in nature. This paper investigates the biomimicry of tafoni, a type of weathered rock that contains pores of varying sizes. The formation of tafoni inspires architectural design, but its complex shape makes manual modeling challenging. The objective of studying the biomimetics of tafoni is to apply its benefits to design applications. Using biomimetic techniques, computation algorithms for tafoni morphogenesis are developed. This paper investigates the inherent characteristics of tafoni and reclassifies them based on architectural geometric elements. It then describes the reclassified tafoni and explains the formation process. This paper develops a 3D evolutionary algorithm and a 2.5D descriptive algorithm based on diagrams. After a comparison, the 2.5D algorithm is chosen because it is more controllable and operable for computational design. This paper also conducts experiments on the results obtained by the 2.5D algorithm to demonstrate its adaptability and architectural design application potential, as well as its application schemes in various design disciplines, including urban planning, architectural design, and landscape design. This paper proposes an algorithm that can be utilized in various fields of computational design. It is computationally efficient while retaining its biological form.